The promise of competency-based education in the health professions for improving global health - Gruppen Larry D; Mangrulkar Rajesh S; Kolars Joseph C (BMC, 2012)
Abstract Competency-based education (CBE) provides a useful alternative to time-based models for preparing health professionals and constructing educational programs. We describe the concept of 'competence' and 'competencies' as well as the critical curricular implications that derive from a focus on 'competence' rather than 'time'. These implications include: defining educational outcomes, developing individualized learning pathways, setting standards, and the centrality of valid assessment so as to reflect stakeholder priorities. We also highlight four challenges to implementing CBE: identifying the health needs of the community, defining competencies, developing self-regulated and flexible learning options, and assessing learners for competence. While CBE has been a prominent focus of educational reform in resource-rich countries, we believe it has even more potential to align educational programs with health system priorities in more resource-limited settings. Because CBE begins with a careful consideration of the competencies desired in the health professional workforce to address health care priorities, it provides a vehicle for integrating the health needs of the country with the values of the profession.